SEMANTIC FEATURES OF BEHAVIORAL VERBS IN ENGLISH AND UZBEK - Elchaev Zohidjon Akhmatovich (Western European Studies, 2023)
This article investigates the semantic features of behavioral verbs in both English and Uzbek languages, shedding light on the nuances that characterize the expression of actions, behaviors, and states of being. The study explores the cognitive dimensions of behavioral verbs in these languages, analyzing how they convey meaning, intention, and emotion. By comparing and contrasting semantic structures, the research aims to deepen our understanding of the linguistic intricacies associated with behavioral verbs in English and Uzbek, providing insights into cross-linguistic variations and cultural influences on the conceptualization of human actions.
Keywords: Behavioral Verbs; Semantic Features; Cross-linguistic Comparison